Legal Politics of Insider Trading Prevention and Enforcement in the Capital Market - Abraham Ethan Martupa Sahat Marune; Arman; Glenn Christian; Muhammad Randhy Adhitya Putra Pratama; Muhammad Fadhil Juliansyah (LEGAL BRIEF, 2023)
This research aims to carry out a legal and political review to insider trading acts perpetrators that can be criminally prosecuted however there have been no cases in Indonesia that have reached court or faced criminal sanctions. The formulation of the problem in this study is: How is the legal politics of preventing and prosecuting insider trading in capital market activities in Indonesia? This study uses a normative juridical method or doctrinal legal research method by collecting data from literature studies. Based on the results of the research, legal politics has been implemented properly, namely through prevention and prosecution. The only thing that has not been regulated is regarding sanctions against parties who obtain material inside information passively and without violating the law. It is necessary to have efforts from public companies in implementing Good Corporate Government through risk mitigation or company regulations related to this principle in order to avoid insider trading actions and Goverment need to regulate sanctions against parties who receive material insider information passively and without against the law in order to create a fair legal market.